Ingratiation and favoritism: Experimental evidence - Stéphane Robin; Agnieszka Rusinowska; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2012)
We provide experimental evidence of workers' by opinion conformity and of managers' discrimination in favor of workers with whom they share similar opinions. In our Baseline, managers can observe both workers' performance at a task and opinions before assigning unequal payoffs. In the Ingratiation treatment, workers can change their opinion after learning that held by the manager. In the Random treatment, workers can also change opinion but payoffs are assigned randomly, which gives a measure of non-strategic opinion conformism. We find evidence of high ingratiation indices, as overall, ingratiation is effective. Indeed, managers reward opinion conformity, and even more so when opinions cannot be manipulated. Additional treatments reveal that ingratiation is cost sensitive and that the introduction of performance pay for managers as well as a less noisy measure of performance increase the role of relative performance in the assignment of payoffs, without eliminating the reward of opinion conformity.
urn:nbn:de:101:1-2012081412625
Keywords: C7; C92; D03; D86; M51; 330; ingratiation; opinion conformity; favoritism; discrimination; social distance; experiment; Leistungsentgelt; Lohndifferenzierung; Meinung; Patronage; Test